2022
DOI: 10.31234/osf.io/f267u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Memory failure predicts belief regression after the correction of misinformation

Abstract: After misinformation has been corrected people initially update their belief extremely well. However, this change is rarely sustained over time, with belief returning towards pre-correction levels. This is called belief regression. The current study aimed to examine the association between memory for the correction and belief regression, and whether corrected misinformation suffers from belief regression more than affirmed facts. Participants from Prolific Academic (N=612) rated the veracity of 16 misinformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Therefore, building on the results of Experiment 1, in Experiment 2 we introduced a one-week delay between reading the articles and completing the test questionnaires. Previous research has found that correction effectiveness is reduced over time (Ecker et al, 2020b;Ecker et al, 2020c;Rich & Zaragoza, 2020;Swire et al, 2017;Swire-Thompson et al, 2023), and of the few studies that have reported familiarity backfire effects, most reported these effects only after a one-week delay (Pluviano et al, 2017(Pluviano et al, , 2019Skurnik et al 2007 [unpublished]). There are also theoretical reasons to expect that a delay may increase the risk of a correction backfiring.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, building on the results of Experiment 1, in Experiment 2 we introduced a one-week delay between reading the articles and completing the test questionnaires. Previous research has found that correction effectiveness is reduced over time (Ecker et al, 2020b;Ecker et al, 2020c;Rich & Zaragoza, 2020;Swire et al, 2017;Swire-Thompson et al, 2023), and of the few studies that have reported familiarity backfire effects, most reported these effects only after a one-week delay (Pluviano et al, 2017(Pluviano et al, , 2019Skurnik et al 2007 [unpublished]). There are also theoretical reasons to expect that a delay may increase the risk of a correction backfiring.…”
Section: Methodsmentioning
confidence: 99%